Бакалаврские и магистерские программы по социологии (опыт Германии в контексте Болонского процесса) - Евтух, В. (Социология: теория, методы, маркетинг, 2008)
The article deals with actual problems of implementation of Bologna process at the level of Bachelor and Master Programs at German universities and other institutions of higher education (Hochschulen), the case of sociology. The analysis is based on material on theoretical and practical aspects of discussion being displayed in the bosom of German sociological community. A special attention is paid to principles of planning and structuring of the education process aimed at training of professional sociologists and adopting their knowledge to needs of European intellectual labor market. The author stresses that the main goal of Bologna process is to approximate education to demands of economic effectiveness. Besides, the important point of the authors view regarding Ukrainian developments is the necessity of concordance between Bologna demands and teaching staff resource of each IHE. The conceptual discussion is attended by concrete examples concerning organizational aspects of educational process in German universities and other institutions of higher education considered from a comparative perspective.